PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK DAN KEPERCAYAAN TERHADAP KEPUASAN KONSUMEN PADA PT. HADJI KALLA CABANG PINRANG - Sitti Sahra Basri; Rachman Suwandaru; Novita Rosanti (Jurnal Sains Manajemen Nitro, 2023)
This study aims to: (1) analyze the effect of service quality on customer satisfaction at PT. Hadji Kalla Pinrang Branch, (2) analyzing the effect of product quality on consumer satisfaction at PT. Hadji Kalla Pinrang Branch, (3) analyzed the effect of trust on consumer satisfaction at PT. Hadji Kalla Pinrang Branch, (4) jointly analyze the effect of service quality, product quality and trust on Toyota customer satisfaction at PT. Hadji Kalla Pinrang Branch. The population of this research is 685 consumers who have bought a car at PT. Hadji Kalla Pinrang Branch. The sample in this study uses the slovin formula, thus the number of samples is 100 consumers. The analytical method used is primary data collected from questionnaires. The results of this study indicate that: service quality has a significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction, trust has a significant effect on customer satisfaction. For the three variables together have an influence on consumer satisfaction, meaning that in building customer satisfaction from the three variables it is very important for companies to do.